Structural Optimization of Lightweight Composite Floors with Integrated Constrained Layer Damping for Vibration Control - Carlos M. C. Renedo; Iván M. Díaz; Jaime H. García-Palacios; Christian Gallegos-Calderón (Actuators, 2023)
Due to current architectural trends, contemporary public buildings are becoming open-plan spaces with much less weight and damping. Consequently, Vibration Serviceability Limit State (VSLS) due to human-induced vibrations has become an increasing concern for structural engineers, especially when designing offices, hospitals, or gymnasiums. When dealing with resonant vibrations, a slight increase in the floor-damping enables decreasing considerably the vibration level. The damping strategy studied in this work is usually known in the literature as Constrained Layer Damping (CLD) and consists of a viscoelastic layer constrained between the concrete slab and the steel beam of a lightweight composite floor. In this paper, a complete structural checking methodology has been developed for analyzing all the limit states that determine the final sizing of a steel–concrete composite floor treated with CLD, including a detailed analysis of the VSLS. The methodology has been used for setting a structural optimization problem for floors with and without CLD treatments. Thus, it has been demonstrated that the integration of CLD treatments at the design stage of the building allows the development of lighter floor structures with a smaller embodied carbon (EC) footprint, especially for long-span schemes with restrictive vibration limitations.